2022
DOI: 10.1101/2022.06.06.494965
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genomic Surveillance of SARS CoV2 in COVID-19 vaccinated healthcare workers in Lebanon

Abstract: The emergence of SARS-CoV-2 variants including the Delta and Omicron along with waning of vaccine-induced immunity over time contributed to increased rates of breakthrough infection specifically among healthcare workers (HCWs). SARS-CoV-2 genomic surveillance is an important tool for timely detection and characterization of circulating variants as well as monitoring the emergence of new strains. Our study is the first national SARS-CoV-2 genomic surveillance among HCWs in Lebanon. We collected 250 samples from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 50 publications
(84 reference statements)
0
4
0
Order By: Relevance
“…The largest scale sequencing attempt however was the one reported by Merhi et al [22] which was the transition period (December 2020 and June 2021) marked by the worldwide gradual replacement of the Alpha variant and the dominance of the Delta. Other sporadic studies were also conducted with different focus groups such as the one by Al Kalamouni et al [23] which revealed the prevalence of BA.1, BA.1.1, and BA.2, Omicron lineages in healthcare workers, between December 2021 and January 2022.…”
Section: Discussionmentioning
confidence: 99%
“…The largest scale sequencing attempt however was the one reported by Merhi et al [22] which was the transition period (December 2020 and June 2021) marked by the worldwide gradual replacement of the Alpha variant and the dominance of the Delta. Other sporadic studies were also conducted with different focus groups such as the one by Al Kalamouni et al [23] which revealed the prevalence of BA.1, BA.1.1, and BA.2, Omicron lineages in healthcare workers, between December 2021 and January 2022.…”
Section: Discussionmentioning
confidence: 99%
“…In Lebanon, the pandemic was defined by the dominance of four SARS-CoV-2 lineages, upon analyzing the whole Lebanese dataset in GISAID [ 20 , 21 ].The genomes available in GISAID show that, by July of 2021, the variant of concern, Delta (B.1.617.2), had already completely substituted Alpha and was, in turn, completely replaced by Omicron (sublineages BA.1 and BA.1.1) by the end of December 2021 [ 20 , 21 ]. Coincidently, the appearances of both lineages (Delta and Omicron) were followed by new surges in the number of cases in Lebanon [ 20 , 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…In Lebanon, the pandemic was defined by the dominance of four SARS-CoV-2 lineages, upon analyzing the whole Lebanese dataset in GISAID [ 20 , 21 ].The genomes available in GISAID show that, by July of 2021, the variant of concern, Delta (B.1.617.2), had already completely substituted Alpha and was, in turn, completely replaced by Omicron (sublineages BA.1 and BA.1.1) by the end of December 2021 [ 20 , 21 ]. Coincidently, the appearances of both lineages (Delta and Omicron) were followed by new surges in the number of cases in Lebanon [ 20 , 21 ]. Accordingly, employees were referred to as SARS-CoV-2 Delta cases if they first tested positive between 1 August 2021, and 20 December 2021, as the majority of the cases in Lebanon were predominantly attributable to the circulating Delta variant during that time [ 20 , 21 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation